Ethical awareness of computer use among undergraduate students - Masrom, Maslin; Ismail, Zuraini; Hussein, Ramlah (ACM New York, 2009)
This study investigates the ethical awareness of computer use among undergraduate computer science students at two public Malaysian universities. One hundred and fifty-nine students were asked to evaluate the code of ethics pertaining to computer ethics. A comparison of undergraduate computer science students between two public universities was done to determine the level of ethical awareness of computer use. Independent Samples t-tests for differences were performed across four distinct groups: university, gender, age, and duration of computer use. The results of the tests conducted indicate that the ethical awareness of computer use of the students differ most significantly on the basis of the university itself. There were minimal differences across gender, age and duration of computer use. This suggests that computer ethics awareness training is needed for university users. The results are discussed and the implications for studies in an educational context are outlined.